Posttranscriptional Regulation Controls Calretinin Expression in Malignant Pleural Mesothelioma - Kresoja-Rakic, Jelena; Sulemani, Merve; Kirschner, Michaela B.; Ronner, Manuel; Reid, Glen; Kao, Steven; Schwaller, Beat; Weder, Walter; Stahel, Rolf A.; Felley-Bosco, Emanuela (Frontiers in Genetics, 2017)
Calretinin (CALB2) is a diagnostic and prognostic marker in malignant pleural mesothelioma (MPM). We previously reported that calretinin expression is regulated at the mRNA level. The presence of a medium sized (573 nucleotide) 3’untranslated region (3’UTR) predicted to contain binding sites for miR-30a/b/c/d/e and miR-9 as well as an A/U-rich element (ARE) in all three transcripts arising from the CALB2 gene, suggests that calretinin expression is regulated via posttranscriptional mechanisms. Our aim was to investigate the role of the CALB2-3’UTR in the posttranscriptional regulation of calretinin expression in MPM. CALB2-3’UTR was inserted downstream of the luciferase reporter gene using pmirGLO vector and reporter expression was determined after transfection into MPM cells. Targeted mutagenesis was used to generate variants harboring mutated miR-30 family and ARE binding sites. Electrophoretic mobility shift assay was used to test for the presence of ARE binding proteins. CALB2-3’UTR significantly decreased luciferase activity in MPM cells. Analysis of mutation in the ARE site revealed a further destabilization of the reporter and HuR binding to the ARE sequence was detected. The mutation of two mir-30 binding sites abolished CALB2-3’UTR destabilization effect; a transient delivery of miR-30e-5p mimics or anti-miR into MPM cells resulted in a significant decrease/increase of the luciferase reporter expression and calretinin protein, respectively. Moreover, overexpression of CALB2-3’UTR quenched the effect of miR-30e-5p mimics on calretinin protein levels, possibly by sequestering the mimics, thereby suggesting a competitive endogenous RNA network. Finally, by data mining we observed that expression of miR-30e-5p was negatively correlated with the calretinin expression in a cohort of MPM patient samples. Our data show the role of I) AU-binding proteins in calretinin stabilization and II) miR-30e-5p in the posttranscriptional negative regulation of calretinin expression via interaction with its 3’-UTR. Furthermore, our study demonstrates a possible physiological role of calretinin’s alternatively spliced transcripts.